ANALYSIS OF CONTEXTUAL TEACHING AND LEARNING METHOD IN TEACHING ENGLISH LANGUAGE AT ELEVENTH GRADE OF SMA NEGERI 1 MANIAMOLO - Saleh, Saleh Mawati Giawa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
Contextual Teaching and Learning method is a learning method that emphasize the process of full student involvement to be able to find the material being studied and relate it to real life situation so as to encourage student to be able to apply it in their lives. This research was aimed at analyzing the implementation of contextual teaching and learning method in teaching English based on the principle of CTL method and the obstacle of teacher experienced at eleventh grade of SMA Negeri 1 Maniamolo. This research was designed by using qualitative research with descriptive qualitative approach. The data was obtained from SMA Negeri 1 Maniamolo School. The data were collected through observation, interview and documentation relate to contextual teaching and learning method. In analyzing the data, the researcher used theory of Miles, Huberman, & Saldana (2014:31-33). In this research, the researchers found that CTL make students be more active in teaching and learning process because students learning material related about their life, students also prefer to practice than to memorizing even though there are some students cannot explain their knowledge by their own language because there are so many students lack of vocabulary and the obstacle experienced by the teacher of using CTL is managing. It is expected that this research would give contribution for the English teacher, it can be used as a method in teaching English to students to develop their knowledge about CTL. And also for the readers, for the next researchers, it can be used as a reference in conducting research related to Contextual Teaching and Learning method